Os educadores sociais e a proteção social em instituições de acolhimento de crianças e adolescentes - Silva, Suélem Lopes (2017)
Whenever the family is not being protective to the children and teenagers, they might have been exposed to risk and vulnerability situations, therefore, the insertion in institutions as a measure of temporary protection could be needed. The function of this institution is going to be to shelter and provide the needed carings to the children and teenagers that, by some reason had to be moved out or abandoned by their families. The team is formed by some professionals, among them, the social educators, which are the focus of this study, since they work directly with the protection measure called Institutional Reception. This paper intends to comprehend the protection of the children and teenagers by the reception, through the view of the social educators. This research has been organized with two articles. The first one aims for comprehending how the protection happens in the Institutional Reception. The second approaches vulnerabilities related to the Institutional Reception. Have taken part of this study 11 social educators aged between 25 and 50 years old. The briefing had been collected in a Institutional Reception for children and teenagers under protection measure in a inner city of Rio Grande do Sul, through semi-structured interviews. The analysis of the briefing was based on the theoretical shapes of the Grounded Theory of Data. Has been established that the protection happens in the reception of children and teenagers, but in some moments it still finds itself vulnerable, mainly because there is not much investment and qualification to the social educators, that works directly to the children and teenagers in protection measure. The reception context, in a way, is promoting vulnerability situations, as for the sheltered public as for the social educators. Points up the necessity of more developed works in the area, as more qualification to the social educators, because, to protect the children and teenagers in shelter, the social educators must be more and more prepared to fill this job extremely important in the Institutional Reception. This way, vulnerability situations will not be promoted in a place that should provide entire protection.